Molecular detection and predisposing factors influencing Anaplasma marginale prevalence in dairy cattle of Chhattisgarh, India - S BISEN; S K SAO; K R BAGHEL; S PAL; S PRUSTY (Indian Journal of Animal Sciences)
Anaplasma marginale, the most common etiological agent of bovine anaplasmosis is an important cause of economic losses in livestock farming, both in the tropical and temperate regions. In the present study, 250 blood samples of cattle from organised and unorganised dairy farms in five districts of the state of Chhattisgarh, India were examined for prevalence of A. marginale. DNA extracted from the blood samples of these cattle was subjected to Polymerase Chain Reaction (PCR) using A. marginale msp1β gene. It resulted in the amplification of 265 bp PCR product in 63.6% (159/250) of animals. The prevalence of anaplasmosis was found to be significantly higher in the animals of organized dairy farms when compared with un-organized farms. Age of cattle seemed to influence the occurrence of infection with young cattle (<1 year) being more susceptible to the pathogen. Relationship between the presence of A. marginale in cattle and certain selected epidemiological factors was also explored. Different cattle breeds seemed to be equally susceptible to A. marginale infection. The study revealed a large cattle population (63.6%) in the study area as carriers of A. marginale infection.